2019
DOI: 10.1530/edm-19-0065
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic hypophosphataemia after intravenous iron therapy: an underrated adverse reaction

Abstract: Summary Iron (ferric carboxymaltose) infusion therapy is used to treat severe iron deficiency which is not responding to the first-line oral iron therapy. However, it can also cause severe renal wasting of phosphate resulting in severe hypophosphataemia in some patients. Despite the growing number of case reports, this side effect is not well known to healthcare professionals. The product labelling information sheet does mention that hypophosphataemia can be a side effect, but also says that this side effect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…iron with erythropoiesis‐stimulating agents, there are no prospective studies showing an increased risk of infection, while others suggest the opposite [25], and current data are conflicting. Finally, the use of ferric carboxymaltose (Ferinject, Vifor Pharma, Glattbrug, Switzerland) has been associated with varying degrees of hypophosphataemia secondary to increased renal losses [26]. While, in the majority of patients, this is transient and asymptomatic, patients with pre‐existing hypocalcaemia, hypophosphataemia, low vitamin D levels or elevated parathyroid hormone levels may be at increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…iron with erythropoiesis‐stimulating agents, there are no prospective studies showing an increased risk of infection, while others suggest the opposite [25], and current data are conflicting. Finally, the use of ferric carboxymaltose (Ferinject, Vifor Pharma, Glattbrug, Switzerland) has been associated with varying degrees of hypophosphataemia secondary to increased renal losses [26]. While, in the majority of patients, this is transient and asymptomatic, patients with pre‐existing hypocalcaemia, hypophosphataemia, low vitamin D levels or elevated parathyroid hormone levels may be at increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although hypophosphatemia related to FCM has been defined as mostly asymptomatic in randomized controlled studies, cases with severe hypophosphatemia, cramps, dizziness, fatigue, nausea, and requiring long-term hospitalization have been reported in the acute period 14,15,18 . In addition, hypophosphatemic osteomalacia and related fractures have been reported in patients receiving repeated doses of therapy in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In the headto-head trials described earlier, severe hypophosphatemia was observed following treatment with FCM, but not with FDI [28] or FER [49]. Although these trials did not report on related symptoms, numerous isolated patient reports describing acute symptomatic hypophosphatemia following treatment with FCM have been published [68][69][70][71][72][73]. In a review paper published in 2017, Zoller et al discussed the long-term complications of hypophosphatemia following IV iron treatment, such as bone fractures and osteomalacia [44].…”
Section: Clinical Consequences Of Hypophosphatemia In the Setting Of IV Iron Treatmentmentioning
confidence: 99%